Effects of Supplier Selection on Procurement Performance of Public Institutions: A Case Study of Southern Division. - Kabugho, Sarah (Kabale University, 2024)
The study assessed the effects of supplier selection on the procurement performance of public institutions. A case study of the southern division. The objectives of the study were; to assess the effect of procurement Planning and organizational Performance of public institutions southern division of Kabale Municipality, to assess the effects of supplier quality commitment on the procurement performance of public institutions of the southern division of Kabale Municipality, and to establish the effect of process cost management of supplier selection on procurement performance of public institutions of southern division Kabale municipality. A descriptive research design was used across a sample of 60 respondents. Data collection tools such as questionnaires and interview guides were used. Findings of the study found that male respondents were more willing to work in the southern division despite the low salaries than female employees. The study concluded that recognizing the importance and risks of supplier selection is critical for effective procurement performance. There is a need for public institutions to adopt a more strategic approach to supplier selection, focusing on reducing risks and improving supplier relationships. Effective supplier selection positively impacts procurement performance by ensuring that procurement activities are sustainable, cost-efficient, and aligned with organizational goals. The study underscores the importance of robust supplier selection processes in achieving optimal procurement performance. The study recommended that public institutions such as the southern division of Kabale municipality should enhance their supplier evaluation criteria to include environmental sustainability, social responsibility, and innovation capabilities. This will ensure that selected suppliers align with the institution’s strategic goals and developing stronger relationships with suppliers through regular communication and collaboration can improve internal coordination and consistency in meeting procurement standards.